MiR-595 and Cldnd1: Potential related factors for bone loss in postmenopausal women with hip osteoporotic fracture. - Sun Jingyue; Liu Peixin; Wang Xiao (PLoS ONE)
Background Recently researches have reported that miRNA and its target genes are associated with osteoporosis. MiRNA and mRNA might be potential diagnostic markers for osteoporosis. Purposes The aim of this study is to explore the potential miRNA and mRNA markers by bioinformatics method and clinical analysis. Patients and methods The miRNA expression profiles were obtained from GSE74209, GSE64433 and GSE115773 in Gene expression Omnibus (GEO). The mRNA expression profiles were obtained from GSE100609. Wayne intersection were used to explore the different expressed miRNAs (DE-miRs). Select the miRNA with the highest Fold Change for subsequent research. Screening of miRNA target genes using TargetScan and miRDB tools. GO and KEGG analyses of target genes (TGs) function were performed. Validate the selected TGs in the GSE100609. We collected female patients with femural intertrochanteric fractures from July 1, 2023 to October 31, 2023. Patient's bone marrow and clinical data were collected. MiRNA and the target mRNA differentially expressed in bone marrow were verified through RT-qPCR. All data were subjected to Shapiro-Wilk test. Using Pearson or Spearman test to detect the correlation between various indicators, and then incorporating indicators related to bone density into multiple linear regression equations. Partial correlation analysis was used to analyze the correlation between the final indicators and bone density. Results A total of 140 DE-miRs were identified. Set the fold change to ">1" and ultimately include 5 miRNAs. Using miR-595 (highest |log2 FC|) as the subject of subsequent research. 3542 targeted mRNAs were predicted from TargetScan and 362 were from miRDB. 337 TGs were intersected, which were mainly enriched in nucleus. Only Cldnd1 were identified using the GSE100609 dataset. We found that miR-595 was highly expressed in patients with high bone mass, while Cldnd1 was downregulated. There was a strong collinearity between miR-595 and Cldnd1. Further multiple linear regression analysis showed a high correlation between miR-595 and bone density. Conclusions These data suggest that miR-595 and Cldnd1 might be related factors for decreased bone mass.